Analysis of Early Childhood Social-Emotional Development Using the EMC2 Approach in Early Childhood Education Institutions - Mushab Al Umairi; Alfiyanti Nurkhasyanah; Abdul Razak Masae (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Children's inability to manage their social and emotional well-being requires strategic intervention through adult support. This study aims to analyze the social and emotional development of early childhood through the implementation of the EMC2 approach in the PAUD environment. This study employed a field research design with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted narratively to describe the opinions, actions, and phenomena observed during the study. Theoretically, this study confirms that the EMC2 approach is effective in mapping and stimulating children's emotional intelligence in formal settings. Practically, the high percentage of students in the